2007
DOI: 10.1080/02791072.2007.10399860
|View full text |Cite
|
Sign up to set email alerts
|

Single Versus Repeated Sessions of Ketamine-Assisted Psychotherapy for People with Heroin Dependence

Abstract: A prior study found that one ketamine-assisted psychotherapy session was significantly more effective than active placebo in promoting abstinence (Krupitsky et al. 2002). In this study of the efficacy of single versus repeated sessions of ketamine-assisted psychotherapy in promoting abstinence in people with heroin dependence, 59 detoxified inpatients with heroin dependence received a ketamine-assisted psychotherapy (KPT) session prior to their discharge from an addiction treatment hospital, and were then rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
115
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(125 citation statements)
references
References 7 publications
1
115
0
2
Order By: Relevance
“…Ketamine, an anesthetic with dissociative and psychedelic properties, has been evaluated in similar settings; it has been found to result in a sustained reduction of drug use in patients with opiate dependence. 92 Griffiths and colleagues have recently demonstrated that psilocybin can promote long-standing increases in spirituality and mysticism, and that the psychedelic session was widely considered by subjects, long afterwards, as one of the most powerful experiences of their lives. 99 This finding suggests that the potential efficacy of such psychoactive substances is due to the production of a so-called transformative experience 97 that precipitates an immediate and persistent change in lifestyle predicated on newfound spirituality.…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine, an anesthetic with dissociative and psychedelic properties, has been evaluated in similar settings; it has been found to result in a sustained reduction of drug use in patients with opiate dependence. 92 Griffiths and colleagues have recently demonstrated that psilocybin can promote long-standing increases in spirituality and mysticism, and that the psychedelic session was widely considered by subjects, long afterwards, as one of the most powerful experiences of their lives. 99 This finding suggests that the potential efficacy of such psychoactive substances is due to the production of a so-called transformative experience 97 that precipitates an immediate and persistent change in lifestyle predicated on newfound spirituality.…”
Section: Discussionmentioning
confidence: 99%
“…Both doses of ketamine also reduced craving for heroin from baseline measures as evaluated by a visual analog scale, however, the high dose was significantly more effective in reducing cravings than the low dose (Krupitsky et al, 2002). A second study ( N = 59) examined the possible benefits of multiple sessions of KPT as opposed to a single session (Krupitsky et al, 2007). Participants randomized to the multiple session treatment had three sessions of drug-assisted KPT in total, and showed significantly greater abstinence at one year follow-up (50%) than those randomized to the single-session group (22.2%; p < 0.05).…”
Section: Introductionmentioning
confidence: 99%
“…Krupitsky and Grinenko (1997) and Krupitsky et al (2002Krupitsky et al ( , 2007 have used this method of ketamine dosing coupled with psychotherapy to aid in the treatment of addictions.…”
Section: Other Clinical Uses Of Ketamine In Psychiatrymentioning
confidence: 99%